(untitled) (People’s Journal of Management, 2025)
Background: Green Education (GE) and Education for Sustainable Development (ESD) have gained prominence as critical frameworks for addressing global sustainability challenges. Despite growing academic interest, the field remains fragmented, with uneven research focus across disciplines, regions, and themes. A systematic analysis of its evolution, key contributors, and knowledge gaps is essential to guide future scholarship and policy. Objective: This study conducts a comprehensive bibliometric analysis to map the GE/ESD research landscape from 2020 to 2024, identifying publication trends, collaboration networks, thematic priorities, and underexplored areas. Methods: Using Lens.org, 1,214 journal articles were extracted and analyzed through VOSviewer (co-authorship, keyword co-occurrence) and WordSift (textual mining). Data were filtered by publication year (2020–2024), document type (articles), and DOI availability. Descriptive statistics, network visualizations, and temporal mappings were employed to assess growth, geographic contributions, and disciplinary intersections. Findings: The analysis revealed four key findings about GE/ESD research from 2020-2024: publication trends showed fluctuating growth with an 18% overall increase, including a pandemic-related 17% decline in 2021 followed by a 26% post-COP28 surge in 2024; geographic distribution was uneven, with China (119 publications), Germany (78), and the U.S. (64) dominating research output while Global South contributions remained limited; thematic analysis identified strong foci on ecology (438 occurrences) and policy (509) but notable gaps in climate change education (65) and health-ESD connections (53); and collaboration patterns appeared fragmented, with underdeveloped international networks and persistent data-quality issues such as misspelled author and journal names compromising analytical precision. These findings collectively highlight both the field’s growth potential and critical areas needing attention to advance comprehensive, inclusive sustainability education research. Conclusion: The study underscores GE/ESD’s interdisciplinary potential but highlights disparities in thematic focus, geographic representation, and collaborative rigor. Addressing these gaps requires standardized terminology, inclusive partnerships, and targeted funding for underrepresented regions and topics. Novelty: This study is among the first to integrate Lens.org data with VOSviewer and WordSift for a dual-method analysis of GE/ESD, offering both macro-level trend mapping and micro-level textual insights. It uniquely identifies missed opportunities in climate education and health-ESD synergies while proposing a roadmap for cohesive field development.